TASYAHUD IBN MAS’UD VERSI KUTUB AL-SITTAH (ANALISIS RIWAYAT BI AL-LAFZHI) - Zainuddin (Institut Agama Islam Darul Ulum Kandangan, 2024)
Usually, mayority of the hadith’s redaction was transmited by meaning, but this studies found that the kutub al-sittah’s writers whose used the variatif sanad whith refered to Ibn Mas’ud as its source, tha fact the hadith of tasyahud praying used riwayat bi al-lafzhi. Although Imam Al-Tirmidzi and Iman Al-Nasa’i informated that Ibn Mas’ud was not only one its source, but this transmison still in habar ahad category because mayority of its sanad used individual system. Besides that Imam Bukhari, Imam Muslim, Imam Ibn Majah and Imam Abu Daud reported the something wrong of Rasulullah’s friends with variatif redaction in matan of hadith as sabab al-wurud, whereas Imam al-Tirmidzi dan Imam al-Nasa’i informated that Rasulullah saw taught them the tasyahud praying. In the same position, four men of mukharrij also reported the explanation of Rasulullah saw in the text of tasyahud with variatif redaction, but no axplanation in transmision of Imam al-Tirmidzi dan Imam al-Nasa’i.